anonymous
  • anonymous
Let f(x) = 9x - 2 and g(x) = -x + 3. Find f(g(x)) HELP? MEDAL AWARD
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
f(x) = 9x - 2 g(x) = -x + 3 f(g(x)) = 9(g(x))-2 = 9(-x+3)-2 =-9x+27-2 =-9x+25
anonymous
  • anonymous
i have a few more ?'s can u help me w them too
anonymous
  • anonymous
let f(x) = x - 2 and g(x) = x2 - 7x - 9. Find f(g(-1)) ??

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
i have to go fairly soon, ill be back on in about 3 hours if you are still on then. i can try to solve maybe one or two in the next 5 minutes
anonymous
  • anonymous
that's all the time i need
anonymous
  • anonymous
f(x) = x - 2 g(x) = x2 - 7x - 9 g(-1) = 2(-1) - 7(-1) - 9 g(-1) = -2 +7-9 g(-1) = -4 f(g(-1) = f(-4) f(-4) = -4 - 2 = -6
anonymous
  • anonymous
so f(g(-1)) = -6
anonymous
  • anonymous
-6 isnt an option -21 -3 3 21
radar
  • radar
f(x) = x - 2 g(x) = x2 - 7x - 9 g(-1) = 2(-1) - 7(-1) - 9 Error is on this line. (-1)^2 =1 not -2 g(-1) = -2 +7-9 g(-1) = -4 f(g(-1) = f(-4) f(-4) = -4 - 2 = -6
anonymous
  • anonymous
hmm, f(g(x)) = (g(x)) - 2 = 2x - 7x - 9 - 2 = -5x -11 = -5(-1) - 11 = 5-11 = -6 im not sure how this is so, could the book possibly be wrong?
anonymous
  • anonymous
no lol
anonymous
  • anonymous
oh, he meant to the power of 2, i didn't realize. i have to go know do u think u could help him from here for me, radar?
anonymous
  • anonymous
i am a her. lol
radar
  • radar
f(x) = x - 2 g(x) = x2 - 7x - 9 g(-1) = -1^2 - 7(-1) - 9 g(-1) =1 +7-9 g(-1) = -1
radar
  • radar
f(x) = x - 2 f(g(-1) = -1 - 2 = -3
radar
  • radar
@alwaysright13, did you see the error which gave a -6 that should be a -1??
anonymous
  • anonymous
yes i did. what about this one ????Let f(x) = x + 8 and g(x) = x2 - 6x - 7. Find f(g(2)).
radar
  • radar
Just repeat the steps using the new function and the new value of 2. g(2)=2^2 - 6(2) -7. Do you see this is the g(x) functrion with 2 substituted for x?
radar
  • radar
This now becomes g(2) = 4 - 12 - 7 = -15 or g(2) = -15 we now use this in the f(x) f(x)=x + 8 f(-15)=-15+8 = -7. Please post any additional problems as a new problem.

Looking for something else?

Not the answer you are looking for? Search for more explanations.